Culinary resilience in a globalized world: how social norms negotiate tradition and adaptation - Morkūnas, Mangirdas; Wang, Yufei; Vilčekova, Lucia (Business, Management and Economics Engineering, 2025)
Purpose – This study investigates how macro-level forces and micro-level cultural constructs shape food culture resilience in different societies. It bridges the knowledge gaps between cultural preservation and adaptation.Research methodology – PLS-SEM methodology was adopted in the survey data of six countries. Bootstrapping verified path coefficients and model robustness.Findings – Cultural Openness supports Heritage, preventing globalization from disempowering myths. Social Pressure drives food culture resilience (FCR) in collectivistic cultures yet is diluted in individualistic settings. Taboos subside in secular/pluralistic settings, replicating trends for moral flexibility. Enhanced predictivity for institutionally institutionalized civilizations facilitates easier observation by the models of modest to considerable FCR variation.Research limitations – Cross-sectional data limit causal inferences. Unmeasured variables could also affect outcomes in transition countries.Practical applications – Strategies should be implemented with cultural correctness by policymakers and marketers. For instance, leveraging openness to redefine traditions in multicultural settings, framing dietetic interventions as collective efforts in collectivist contexts, and customizing products with flexible ethical schema in secular settings.Originality/Value – This research fills macro-micro cultural theory gaps, suggesting “adaptive preservation” as a driver of traditions in a globalizing world. This research shakes homogenization discourses, providing a rich model for cultural.